Action research on enhancing role effectiveness of the Ministry of Liturgical Music of San Antonio de Padua Parish - Bisquera, Mary Joanne DT. (Animo Repository, 2021)
In this action research, I focused on a research opportunity in our parish which we collaboratively identified to determine effectiveness of the choir groups under the Ministry of Liturgical Music in their role to lead the congregation in singing during Eucharistic celebrations, and improve or enhance their effectiveness. Group effectiveness is defined by Guzzo and Dickson (1996) as group-produced outputs, the consequences a group has for its members or the enhancement of a team’s capability to perform effectively in the future. There were conflicting views among the choir heads about their assessment about the congregation being able to join the choir in singing during Sunday masses. This action research was developed with the objectives of: (1) identifying how the choir groups are doing in terms of leading the congregation in singing during Sunday masses by conducting a survey among the parishioners; (2) increasing or maintaining the participation rate of the congregation in singing during Sunday masses based on the results of the survey by 90% to 100%; and (3) reviewing and improving the organizational conditions that would contribute to the effectiveness of the choir groups in leading the congregation in singing during masses. As an insider action researcher, I applied triangulation of data in data generation by using different methods of data collection such as pure inquiries, focus group discussions and observation. In addressing the opportunity, I was guided by Hackman’s Normative Model of Group Effectiveness and Kurt Lewin’s Change Management Model. We identified the components and determinants of group effectiveness and organizational conditions contributing to group effectiveness which we needed to work on and used Lewin’s Change Management Model to effect change in the organization. The first cycle of intervention focused on conducting a survey among parishioners to determine effectiveness of the choir groups in leading the congregation in singing during Sunday masses. Our second cycle focused on reviewing the current status of the choir groups that would contribute to the enhancement of their effectiveness by ensuring that the unified line-up of songs is being used by all the choir groups. These activities were successful in achieving our objectives for this project. In doing this project, I realized that there is something that we can do as a Ministry to further assess how we are doing in terms of fulfilling our role. I learned to become more proactive in collaborating with our choir heads about all the other challenges that our choir group and the Ministry are facing. Following the two action research cycles, I recommend establishing a platform for parishioners where they can provide feedback, if any, not just on the services of the choir groups in encouraging congregational singing during masses but also feedback towards the services of other parish lay ministers.